Tuberculosis endemicity and BCG vaccination: Protection against COVID-19 - Boppana, Tarun Krishna; Mittal, Saurabh; Madan, Karan; Mohan, Anant; Hadda, Vijay; Guleria, Randeep (Monaldi Archives for Chest Disease, 2022)
The coronavirus disease 2019 (COVID-19) has affected different countries in a differential manner. The host susceptibility and host factors are important parameters for this variability. This study aimed to assess the effect of tuberculosis (TB) endemicity and Bacille Calmette-Guerin (BCG) coverage on COVID-19. Available data regarding TB incidence, BCG coverage (as per the World Health Organization), and COVID-19 incidence of 168 countries as of 19th September 2021was collected. Countries were divided into four cohorts based upon annual TB incidence and BCG coverage and COVID-19 incidence and case fatality rates were compared using the Kruskal-Wallis test. Countries with low TB incidence and low BCG coverage had the highest COVID-19 incidence per lac population. However, no significant difference was seen in COVID-19 cases fatality rate. Higher TB incidence and BCG coverage were associated with lesser incidence of COVID-19. This result paves the way for research into pathogenesis and host immune response in COVID-19.